Ultimum Remedium Principles: Realizing Restorative Justice For Children In Conflict With The Law - Wagiman, Wagiman; Jubaidi, Didi (KRTHA BHAYANGKARA, 2024)
This research analyzes the extent to which the concept of the Ultimum Remedium Principle becomes the principle basis for judges to keep children out of prison. This principle encourages problem-solving efforts involving perpetrators, victims and other parties. The provisions of Law No. 11/2012 are a form of certainty in providing clear guidelines for judges in making decisions that are optimal for the interests of children, in accordance with the principle of the Ultimum Remedium Principle. Nonetheless, some judges still tend to take action based on the theory of retaliation when determining responsibility for the wrongdoing committed by the child. This study aims to determine the extent to which this country has a legal umbrella in protecting children and to determine the optimization of the application of the ultimum remedium principle to crimes committed by children. This research is a normative juridical study. The results showed that the settlement of cases of children in conflict with the law according to Law No. 11/2012 is to prioritize alternative out-of-court settlements which are the basic principles in the legal system governing child protection. This approach is in line with the principles of human rights and the best interests of the child.